An analysis of Students’ Motivation to Speak through Information Gap Task Activities - Santri, Sulfi (IAIN KENDARI, 2022)
This qualitative research aims to determine the extent to which students are motivated to speak through information gap activities in English classroom at one of high schools in Kota Kendari. This research was conducted in three meetings consisting of two meetings with activity stages including: planning, implementing the action, observing (observing), and reflecting. The data was gathered using field observation sheets and student reflection sheets. The research findings reveal that the information gap activity can motivate students to speak in English class. Students look enjoy, happy, and enthusiastic in the classroom. Students are motivated to speak when they are assigned information gap activities in pairs or groups. The activities give them more opportunities to practice speaking by exchanging certain information to other friends. Students are encouraged to communicate and collaborate with their partners in completing the tasks.